Iatrogenic gall bladder perforations in laparoscopic cholecystectomy: an audit of 200 cases - Zubair, M; Habib, L; Mirza, MR; Channa, MA; Yousuf, M (Mymensingh Medical Journal, 2010)
Mymensingh Med J. 2010 Jul;19(2):422-6 The abstract of this article is available on the PubMed website